The Upper Motor Neuron—Improved Knowledge from ALS and Related Clinical Disorders - Parvathi Menon; Steve Vucic (Brain Sciences, 2021)
Upper motor neuron (UMN) is a term traditionally used for the corticospinal or pyramidal tract neuron synapsing with the lower motor neuron (LMN) in the anterior horns of the spinal cord. The upper motor neuron controls resting muscle tone and helps initiate voluntary movement of the musculoskeletal system by pathways which are not completely understood. Dysfunction of the upper motor neuron causes the classical clinical signs of spasticity, weakness, brisk tendon reflexes and extensor plantar response, which are associated with clinically well-recognised, inherited and acquired disorders of the nervous system. Understanding the pathophysiology of motor system dysfunction in neurological disease has helped promote a greater understanding of the motor system and its complex cortical connections. This review will focus on the pathophysiology underlying progressive dysfunction of the UMN in amyotrophic lateral sclerosis and three other related adult-onset, progressive neurological disorders with prominent UMN signs, namely, primary lateral sclerosis, hereditary spastic paraplegia and primary progressive multiple sclerosis, to help promote better understanding of the human motor system and, by extension, related cortical systems.